2007
DOI: 10.1093/toxsci/kfm084
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-Induced Neuronal Cell Death in the Perinatal Rhesus Monkey

Abstract: Ketamine is widely used as a pediatric anesthetic. Studies in developing rodents have indicated that ketamine-induced anesthesia results in brain cell death. Additional studies are needed to determine if ketamine anesthesia results in brain cell death in the nonhuman primate and if so, to begin to define the stage of development and the duration of ketamine anesthesia necessary to produce brain cell death. Rhesus monkeys (N = 3 for each treatment and control group) at three stages of development (122 days of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
524
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 551 publications
(555 citation statements)
references
References 51 publications
22
524
2
4
Order By: Relevance
“…Activation of NMDARs is essential for long-term potentiation and spatial learning and memory (Malenka and Bear, 2004), and NMDAR blockade results in impaired synaptic plasticity manifested as adverse effects on learning and memory (Sakimura et al, 1995;Shimizu et al, 2000). It has been shown that higher doses of ketamine can induce neuroapoptosis in rodents (Maxwell et al, 2006;Olney et al, 2002a;Wang et al, 2005) and primates (Haberny et al, 2002;Slikker et al, 2007b;Wang et al, 2006) during early development. In agreement, we have previously reported that ketamine induces motor neuron toxicity in zebrafish embryos .…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NMDARs is essential for long-term potentiation and spatial learning and memory (Malenka and Bear, 2004), and NMDAR blockade results in impaired synaptic plasticity manifested as adverse effects on learning and memory (Sakimura et al, 1995;Shimizu et al, 2000). It has been shown that higher doses of ketamine can induce neuroapoptosis in rodents (Maxwell et al, 2006;Olney et al, 2002a;Wang et al, 2005) and primates (Haberny et al, 2002;Slikker et al, 2007b;Wang et al, 2006) during early development. In agreement, we have previously reported that ketamine induces motor neuron toxicity in zebrafish embryos .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a recent investigation of perinatal Rhesus monkeys, there was no evidence of apoptosis subsequent to a three-hour infusion of ketamine. 15 The final chapter on this subject remains to be written.…”
mentioning
confidence: 99%
“…15 A total of 61 patients have been diagnosed with PRIS, with 20 deaths in children and 18 in adults. 16 Although Diprivan® has been approved for use in humans since 1989, PRIS was not reported until 1992.…”
mentioning
confidence: 99%
See 2 more Smart Citations